Does social policy through rent controls inhibit new construction? Some answers from long-run historical evidence - Konstantin A. Kholodilin; Sebastian Kohl (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The (re-)introduction of rent regulation in the form of rent controls, tenant protection or supply rationing is back on the agenda of policymakers in light of rent inflation in many global cities. While rent control as social policy promises short-term relief, economists point to their negative long-run effects on new construction. This paper present long-run data on both rent regulation and housing construction for 16 developed countries (1910-2017) and 44 developing countries since the 1980s to confirm the economists' view generally, albeit with certain reservations. The negative effect of regulation can be offset by exemptions for new construction, by compensating government construction and by a flight of new construction into the owner-occupied sector. The overall magnitude of the effect is therefore not as high as expected and shows non-linearities. But, although rent control is usually introduced with good social-policy intentions, it generally risks to crowd out its object of regulation through inhibiting new construction.
Keywords: C23; O18; R38; 330; residential construction; rent control; tenure security; housing rationing; panel data model